Implementing ISO 9000 - 2000 : the journey from conformance to performance / Tom Taormina and Keith Brewer. - Taormina, Tom (Prentice Hall PTR, 2001)
The theme of this ISO 9000 text is how to move from the ISO standard being an overhead expense to a profit centre within an organisation.